Muskat Problem with Surface Tension (Journal of Partial Differential Equations, 1997)
In this paper, we consider Muskat problem with surface tension at the free boundary. Under the natural conditions, we prove tbe existence of classical solution locally in time by Schauder fixed point theorem.